Modeling of hydrodynamics of fine particles deposition in packed-bed reactors. (December 2017) - Rabbani, Shahid; Sassi, Mohamed; Shamim, Tariq
With the passage of time for chemical operations involving packed-bed reactors, especially in petroleum refining and petrochemical industries, non-filterable fines such as coke, corrosion products and fine clay in oilsands bitumen deposit on the catalyst particles. The gradual entrapment and deposition of fine particles of range 0.7–20 µm cause the pore-plugging phenomenon to occur which consequently blocks the flow passages inside the porous medium. To understand the plugging phenomenon and its effect on hydrodynamic of the reactor, we developed a computational fluid dynamics model which is based on reactor collection efficiency, filtration rate, Brownian motion and interfacial momentum exchange terms to simulate the pressure drop due to deposition of fine particles in real conditions. With the help of this model, we have studied the effect of fines deposition on bed porosity and clogging. This is for the first time that Ansys Fluent has been used to simulate fine-particle deposition in packed-bed conditions. The result was a Eulerian–Eulerian 2-D computational fluid dynamics model which considered all the three phases, i.e. liquid, catalyst and fine particles. The results were validated against the experiments reported in the literature and reached good agreement.